OIL GLANDS IN PTERODON PUBESCENS BENTH. (LEGUMINOSAE-PAPILIONOIDEAE): DISTRIBUTION, STRUCTURE, and SECRETION MECHANISMS - Rodrigues, Tatiane M. [UNESP]; Machado, Silvia R. [UNESP] (Univ Chicago Press, 2012)
Pterodon pubescens Benth., a legume of the Brazilian Cerrado, produces oil that is employed in folk and conventional medicine. In this study, we investigated the distribution, structure, and secretion mechanisms of the secretory cavities in the mature embryo, seedlings, and vegetative organs of adult plants of P. pubescens, using light and electron microscopy as well as cytochemical methods (ZIO). Secretory cavities occur in the epicotyl and eophylls of seedlings and in the primary stem and leaves of adult plants, and they are absent in the embryo. These cavities are constituted by a wide lumen and a uniseriate epithelium of secretory cells. A parenchyma sheath surrounds each gland. Oils and terpenes were histochemically detected in the epithelium and in the lumen of the cavities. Ultrastructurally, epithelial cells showed proliferation of endoplasmic reticulum, abundant mitochondria, polyribosomes, polymorphic plastids, and lipid droplets. Multivesicular bodies and paramural bodies were also common in these cells. The secretion was released from the protoplast of the epithelial cells toward the lumen by eccrine, granulocrine, and holocrine mechanisms. The features of sheath cells evidenced by ZIO, such as the presence of Golgi bodies and smooth endoplasmic reticulum, indicate that these cells have secretory activity and participate in producing secretions.
Keywords: anatomy; cell ultrastructure; Leguminosae; secretory cavity